PENGARUH PEMBERIAN KOMPOS PELEPAH KELAPA SAWIT DAN PUPUK NPKMg TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Eaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Yulianto, Andika Wahyu; Sarman, Sarman; Swari, Elly Indra (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2024)
Oil palm is a plantation commodity that plays an important role in advancing the country's economy. Jambi Province is one of the centers of oil palm plantations in Indonesia. dominated by smallholder plantations which are generally managed in an inaccurate way, causing Jambi Province's oil palm productivity (3,506 kg/ha) to be lower than the National productivity (3,873 kg/ha) and resulting in the expansion of the TTM/TR area. The purpose of this study was to study the effect of applying and obtaining the best dose of palm frond compost and NPKMg fertilizer on the growth of oil palm seedlings (Elaeis guineensis Jacq.). This research was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi and lasted for months, starting from July-October 2022. This study used a Randomized Block Design (RBD) with 6 treatments, namely: p0 = 100% NPKMg (recommendation), p1 = 20% palm frond compost + 80% NPKMg (R), p2 = 40% palm frond compost + 60% NPKMg (R), p3 = 60% palm frond compost + 40% NPKMg (R), p4 = 80% palm frond compost + 20% NPKMg (R), p5 = 100% palm frond compost. Variables observed included height increase (cm), increase in tuber diameter (mm), increase in the number of leaves (strands), shoot dry weight (g), root dry weight (g) and root crown ratio. The results showed that the application of palm frond compost and NPKMg fertilizer was able to increase growth in the variable increase in weevil diameter and increase in the number of leaves. However, it has not been able to increase the increase in seedling height, shoot dry weight and root dry weight and obtain a good root canopy ratio. Dosage of 60% palm frond compost + 40% NPKMg gave the best average growth of 6 months old oil palm seedlings in the main nursery. In addition, applying palm frond compost can reduce the use of NPKMg fertilizer by 60% or 30 g/seed. Keywords : Main Nursery, Palm Frond Compost, NPKMg Fertilier